Dependence with air density of the response of the PTW SourceCheck ionization chamber for low energy brachytherapy sources. Issue 12 (22nd November 2013) - Tornero‐López, Ana M.; Guirado, Damián; Perez‐Calatayud, Jose; Ruiz‐Arrebola, Samuel; Simancas, Fernando; Gazdic‐Santic, Maja; Lallena, Antonio M.
Abstract : Purpose: : Air‐communicating well ionization chambers are commonly used to assess air kerma strength of sources used in brachytherapy. The signal produced is supposed to be proportional to the air density within the chamber and, therefore, a density‐independent air kerma strength is obtained when the measurement is corrected to standard atmospheric conditions using the usual temperature and pressure correction factor. Nevertheless, when assessing low energy sources, the ionization chambers may not fulfill that condition and a residual density dependence still remains after correction. In this work, the authors examined the behavior of the PTW 34051 SourceCheck ionization chamber when measuring the air kerma strength of 125 I seeds. Methods: : Four different SourceCheck chambers were analyzed. With each one of them, two series of measurements of the air kerma strength for 125 I selectSeed TM brachytherapy sources were performed inside a pressure chamber and varying the pressure in a range from 747 to 1040 hPa (560 to 780 mm Hg). The temperature and relative humidity were kept basically constant. An analogous experiment was performed by taking measurements at different altitudes above sea level. Results: : Contrary to other well‐known ionization chambers, like the HDR1000 PLUS, in which the temperature‐pressure correction factor overcorrects the measurements, in the SourceCheck ionization chamber they are undercorrected. At a typical atmospheric situation of 933 hPa (700 mm Hg) and 20 °C, this undercorrection turns out to be 1.5%. Corrected measurements show a residual linear dependence on the density and, as a consequence, an additional density dependent correction must be applied. The slope of this residual linear density dependence is different for each SourceCheck chamber investigated. The results obtained by taking measurements at different altitudes are compatible with those obtained with the pressure chamber. Conclusions: : Variations of the altitude and changes in the weather conditions may produce significant density corrections, and that effect should be taken into account. This effect is chamber‐dependent, indicating that a specific calibration is necessary for each particular chamber. To our knowledge, this correction has not been considered so far for SourceCheck ionization chambers, but its magnitude cannot be neglected in clinical practice. The atmospheric pressure and temperature at which the chamber was calibrated need to be taken into account, and they should be reported in the calibration certificate. In addition, each institution should analyze the particular response of its SourceCheck ionization chamber and compute the adequate correction factors. In the absence of a suitable pressure chamber, a possibility for this assessment is to take measurements at different altitudes, spanning a wide enough air density range.